A cluster-randomized trial to estimate the effect of mobile screening and treatment feedback on HbA1c and diabetes-related complications in Tshwane primary health care clinics, South Africa - Webb, Elizabeth Melanie (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2017)
• Screening improved significantly with a dedicated team using a mobile unit. • The study focussed on both process and outcome indicators to monitor care. • The cluster design allowed for minimal bias and contamination. • Primary and tertiary care interaction to improve care should be further explored.